2013
DOI: 10.14214/sf.903
|View full text |Cite
|
Sign up to set email alerts
|

The contradictory role of understory vegetation on the success of Scots pine regeneration

Abstract: The contradictory role of understory vegetation on the success of Scots pine regenerationHyppönen M., Hallikainen V., Niemelä J., Rautio P. (2013). The contradictory role of understory vegetation on the success of Scots pine regeneration. Silva Fennica vol. 47 no. 1 article id 903. 19 p. AbstractIn North-East Finland, severe problems have been encountered in the natural regeneration of Scots pine (Pinus sylvestris L.) on sites where regeneration through site preparation usually is quite successful. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
4
17
0
1
Order By: Relevance
“…A minimum of 2000 ha −1 (4 seedlings per subplot) denotes a sufficient regeneration density for Scots pine (e.g. Hyppönen et al 2013). In our study, we found that at least 4 seedlings per subplot (2500 seedlings ha −1 ) were present in 99 % of the subplots suggesting regeneration success and good management practices.…”
Section: Factors Underlying Scots Pine Regeneration In Central Spainsupporting
confidence: 55%
“…A minimum of 2000 ha −1 (4 seedlings per subplot) denotes a sufficient regeneration density for Scots pine (e.g. Hyppönen et al 2013). In our study, we found that at least 4 seedlings per subplot (2500 seedlings ha −1 ) were present in 99 % of the subplots suggesting regeneration success and good management practices.…”
Section: Factors Underlying Scots Pine Regeneration In Central Spainsupporting
confidence: 55%
“…Prescribed burning is often recommended for creating suitable ground for pine (Hyppönen et al 2013), but together with postfire clearing, it may favor ericaceous species that reduce the available nitrogen of the already nutrient-stressed habitat (Mallik 2003), affecting especially pine and other conifers, and may lead to continuous cover of Calluna (Norberg et al 2001). Some studies have shown that pine best regenerates 5 years after fire (Marzano et al 2012), but it may be delayed by competing vegetation, especially the presence of Calluna (Mallik 2003), which may cause conversion of forestland into heathland that may persist for up to 50 years after fire (Norberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of the forest floor in boreal forests is covered by mosses [1,2], and therefore, the rejuvenation of the stand is likely to be influenced by the properties of the moss layer. Rejuvenation of coniferous seedlings appears particularly difficult in forests with an abundant moss presence [3,4], because mosses can outcompete seedlings for resources, such as light, space [5,6] and nutrients [7,8]. Previous work has also shown that these negative effects of mosses on seedlings can vary depending on a variety of external factors, such as the degree of abiotic stress [6,9] and other site characteristics (e.g., the type of growth substrate beneath the mosses) [5,10].…”
Section: Introductionmentioning
confidence: 99%